2004
DOI: 10.1007/s00125-003-1263-9
|View full text |Cite
|
Sign up to set email alerts
|

Beta-cell dysfunction and glucose intolerance: results from the San Antonio metabolism (SAM) study

Abstract: Aims/hypothesis. Both insulin resistance and beta-cell dysfunction play a role in the transition from normal glucose tolerance (NGT) to Type 2 diabetes (T2DM) through impaired glucose tolerance (IGT). The aim of the study was to define the level of glycaemia at which beta-cell dysfunction becomes evident in the context of existing insulin resistance. Methods. Insulin response (OGTT) and insulin sensitivity (euglycaemic insulin clamp) were evaluated in 388 subjects in the San Antonio Metabolism (SAM) study (138… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

16
243
1
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 307 publications
(263 citation statements)
references
References 61 publications
16
243
1
3
Order By: Relevance
“…A similar observation has been reported in children [2], although most previous studies have demonstrated a decrease in insulin sensitivity in adults with an FPG >6.1 mmol/l (110 mg/dl) [3,4]. The defect in first-phase insulin secretion is reminiscent of the decline in insulin secretion observed in normal glucose-tolerant subjects with 2-h plasma glucose concentrations well within the normal range, reported by Gasteldelli and colleagues [5]. Both observations [1,5] suggest that the current cut-off values that define normal glucose tolerance do not correspond to plasma glucose levels that identify the presence of physiological alterations in insulin secretion in vivo.…”
supporting
confidence: 80%
“…A similar observation has been reported in children [2], although most previous studies have demonstrated a decrease in insulin sensitivity in adults with an FPG >6.1 mmol/l (110 mg/dl) [3,4]. The defect in first-phase insulin secretion is reminiscent of the decline in insulin secretion observed in normal glucose-tolerant subjects with 2-h plasma glucose concentrations well within the normal range, reported by Gasteldelli and colleagues [5]. Both observations [1,5] suggest that the current cut-off values that define normal glucose tolerance do not correspond to plasma glucose levels that identify the presence of physiological alterations in insulin secretion in vivo.…”
supporting
confidence: 80%
“…We have shown elsewhere [3], using published data from some of the authors of Mari et al and DeFronzo et al [4], that glycaemic responses to an OGTT conform closely to a simple HOMA-like model [5] relating insulin secretion, insulin sensitivity and glycaemia. The model can be expressed as:…”
mentioning
confidence: 72%
“…That this model provides a strong fit to data (r 2 =0.83 for both fasting and 2 h OGTT responses [4]) is not proof that it is fundamentally true or complete. However, it demonstrates that, in this data set at least, the model can explain all the variation that is not due to likely measurement and within-subject errors.…”
mentioning
confidence: 92%
See 2 more Smart Citations